Medicinal management of oral submucous fibrosis in the past decade- A systematic review - Chandramani B. More; Deepa Jatti Patil; Naman R. Rao (Journal of Oral Biology and Craniofacial Research)
Introduction: Oral submucous fibrosis (OSMF) is a potentially malignant disorder with a high rate of malignant transformation. It is associated with chewing of areca nut and tobacco products with a high global prevalence, particularly in the southeast Asian countries. A wide range of treatment modalities are available, ranging from corticosteroids, antioxidants, nutritional supplements to herbal medicines but lacks a reliable treatment regimen. Aim: This systematic review will comprehensively analyze the medicinal treatment for OSMF from 2011 to 2020, apprise the literature with new clinical studies, and initiate a discussion about other potential medicines. Material and methods: A comprehensive electronic search was conducted in Pubmed, Scopus, and other databases from January 2011 to June 2020 according to the PRISMA guidelines, to identify all the clinical studies for the medicinal management of OSMF with definite keywords and defined criteria. Results: Among the thirty-two included clinical studies 23 were randomized controlled studies and 9 were case-control studies. The treatment outcomes were diverse, and the majority of the studies showed improvement in the subjective signs and symptoms of OSMF. Only a few studies noticed the side effects. Conclusion: No single treatment modality is effective in the management of OSMF. The concurrent use of triple therapy is efficacious. The naturally occurring herbal medicines have an immense potential in the management of OSMF. Therefore, high-quality, longitudinal, multi-center randomized controlled trials with larger samples need to be conducted to further assess the efficacy of various medicinal formulations in conjunction with physiotherapy in the management of OSMF.